The synthesis of annulated 4-alkylidenebutenolides from naturally occurring diosphenols - Viljoen, Murray S.(Murray Stephen) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D..) -- University of Stellenbosch, 1998.